FROM CAMERA AS PART OF THE BODY, TO CAMERA – THE BODY PART - Dimitrijevič, Danica (Design/Arts/Culture, 2023)
The digital world is where 3.4 billion people communicate via digital images through social media. On average, each one of us spends 6 hours each day in front of a screen. The digital images rapidly appearing and disappearing under our scrolling fingers shape our perception, time and body movements, brain structure, and responses in a complex neurological way. The camera enables the formation of our identity, social development, aesthetic value, and cultural participation. Without this camera image, one is isolated, unable to speak. Moreover, without storage where we save images, we are exempt from personal history, narratives, and memory. Once we integrated a camera into the smartphone, we produced an extra organ. With the Orion visual cortical prosthesis medical study that implants a camera into the eyes to restore vision, face emotional surveillance project VibeCheck, and BeAnotherLab software, swooping through virtual reality the bodies, this article follows the socio-philosophical and technological shifts through the history of the camera and photography in object production, body perception, their definition, interaction, and final merge between body and camera object. Through the reference of the theoretical works of Roland Barthes, Maurice Merleau-Ponty, Karen Barad and Tim Ingold, the article follows how we have produced camera images through time and how camera images have been producing us. The camera transforms from a separate room or device to a prosthetic/inherent part of the body, without which the body is not fully functional. Today, a person without a phone camera is marginalized and handicapped. The deficit of not having an image-generating tool turns out to be a sensual deprivation, social limitation and discrepancy in identity.